Congenital cutis laxa syndrome: type II autosomal recessive inheritance - Tüysüz, Beyhan; Arapoğlu, Müjde; Ilikkan, Barbaros; Demirkesen, Cuyan; Perk, Yildiz (The Turkish Journal of Pediatrics, 2003)
Cutis laxa is a term that refers to markedly loose skin that is not hyperelastic. It is regarded as a genetically heterogeneous group of diseases and is presently divided into five types. We report a male patient with type II autosomal recessive disease. The patient was the third child of first-cousin consanguineous, healthy parents. His two siblings died a few hours after birth. One of the siblings also had similar features and wrinkled skin. Our case had markedly loose and wrinkled skin especially over the dorsum of the hands and feet, and on the face and abdomen, dolichocephaly, hypertelorism, blepharochalasis, long filtrum, pectus excavatus, large fontanelles, prominent low-set ears and umbilical hernia. These findings and skin biopsy were consistent with cutis laxa syndrome. In addition to these findings, consanguinity, atypical facies, large fontanelles and umbilical hernia were typical manifestations of type II autosomal recessive cutis laxa.